Bone Mineral Density Assessment With Relugolix Combination Therapy: Results From the Phase 3 LIBERTY Program [OP04-2D]. (May 2020) - McClung, Michael R.; Santora, Arthur C.; Al-Hendy, Ayman; McKain, Laura; Pazirandeh, Jessica; Wagman, Rachel B.
Abstract : INTRODUCTION: In phase 3 Institutional Review Board-approved LIBERTY 1 and 2 studies, relugolix combination therapy (Relugolix-CT [once daily relugolix 40 mg, estradiol 1.0 mg, norethindrone acetate 0.5 mg]) significantly reduced menstrual blood loss (MBL) in women with heavy menstrual bleeding associated with uterine fibroids (UF). We assessed the effects of Relugolix-CT in preventing bone loss from estrogen deprivation associated with GnRH receptor antagonist monotherapy. METHODS: Premenopausal women (age 18–50 years) with MBL volume ≥80 mL/cycle were randomized 1:1:1 to receive Relugolix-CT for 24 weeks, relugolix 40 mg alone for 12 weeks followed by Relugolix-CT for 12 weeks (delayed Relugolix-CT), or placebo for 24 weeks. Bone mineral density (BMD) by dual energy X-ray absorptiometry of the lumbar spine (LS) (L1–4), total hip, and femoral neck was assessed at screening and Weeks 12 and 24. Percent change from baseline between treatment groups was summarized by location using a mixed-effect model adjusted for region, visit and selected baseline characteristics. RESULTS: In LIBERTY 1 (N: 387), mean % changes from baseline at 24 weeks in LS BMD for Relugolix-CT and placebo were -0.36% and 0.05%, respectively and delayed Relugolix-CT was -1.82%. In LIBERTY 2 (N: 381), mean % changes from baseline in BMD at LS for Relugolix-CT and placebo were -0.13% and 0.32%, respectively, and delayed Relugolix-CT was -2.12%. CONCLUSION: Compared with relugolix monotherapy, relugolix-CT preserves bone mass over 24 weeks. Initiating treatment for UF with relugolix combined with E2/NETA represents a potential method for preserving BMD while providing therapeutic benefit over the long-term.